Coccidiosis in Livestock, Poultry, Companion Animals and Humans - Dubey, J. P. (Boca Raton, FL : CRC Press, 2020)
Coccidiosis is one of the most important diseases of livestock, particularly poultry, with billions of dollars spent on prevention worldwide. The disease is so important and pervasive that until recently, all poultry feed was medicated with coccidiostats, mainly antibiotics. With the rapid development of drug resistance, the search is on for alternative methods of control of coccidiosis in poultry. With chapters authored by internationally renowned scientists, this book covers coccidiosis in all major livestock species, including cattle, sheep, and goats. Special emphasis is given to poultry coccidiosis given the significant economic impact, and another chapter looks at intestinal coccidiosis in humans, including Cyclospora. Chapters discuss techniques, molecular biology, host-pathogen immunobiology and immunoprophylaxis, genetics and genomics, biology, and chemotherapy. Despite an explosion of research in the last 40 years, there has been no new book published discussing conventional coccidiosis for more than 25 years. This comprehensive review therefore answers an urgent need for a book dealing exclusively with conventional coccidia (Cystoisospora, Cyclospora). It provides concise, authoritative, up-to-date information on coccidiosis, with particular attention given to research in the last 28 years. This book is essential reading for any practitioner or researcher involved in livestock production, including biologists, veterinarians, parasitologists, and researchers from government, academia, and industry.
6.3.3.3 Australia
OCLC-licensed vendor bibliographic record.
Keywords: MEDICAL / Veterinary Medicine / General; MEDICAL / Veterinary Medicine / Food Animal; SCIENCE / Life Sciences / General; Coccidiosis; Coccidiosis in animals; Coccidia